2003
DOI: 10.1164/rccm.200211-1262oc
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Cigarette Smoke Decreases Lung cAMP and Increases Airway Hyperresponsiveness

Abstract: Epidemiologic studies suggest that in utero exposure to tobacco smoke, primarily through maternal smoking, increases the risk for asthma in children; however, the mechanism of this phenomenon is not clear. Cyclic adenosine monophosphate relaxes airway smooth muscles in the lung and acts as an antiasthmatic. In this study, we examined the effects of in utero cigarette smoke exposure of Balb/c mice on airway responsiveness, as determined by Penh measurements. Animals exposed prenatally but not postnatally to cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
59
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 53 publications
7
59
0
Order By: Relevance
“…Smoke extract significantly reduced A 2A -stimulated PKA, and was mediated by the smoke extract reduction of cAMP concentrations. These data further support earlier studies that revealed how cigarette smoke exposure decreases cAMP concentrations (49). Cigarette smoke has also been documented to activate PKC (50), and considering the differential roles of PKA and PKC, we investigated the smoke extract-mediated activation of PKC, and found a robust activation of PKC in A 2A -stimulated wounded epithelial cells exposed to smoke extract.…”
Section: Discussionsupporting
confidence: 90%
“…Smoke extract significantly reduced A 2A -stimulated PKA, and was mediated by the smoke extract reduction of cAMP concentrations. These data further support earlier studies that revealed how cigarette smoke exposure decreases cAMP concentrations (49). Cigarette smoke has also been documented to activate PKC (50), and considering the differential roles of PKA and PKC, we investigated the smoke extract-mediated activation of PKC, and found a robust activation of PKC in A 2A -stimulated wounded epithelial cells exposed to smoke extract.…”
Section: Discussionsupporting
confidence: 90%
“…In mouse offspring exposed to maternal smoking in utero, MCh responsiveness was reportedly associated with a decreased presence of cyclic AMP in lung tissue [18]. This is of interest, since cyclic AMP is involved in relaxation of smooth muscle in the airway.…”
Section: Discussionmentioning
confidence: 98%
“…We used BALB/c mice for three reasons: (1) BALB/c mice are a well-accepted strain for asthma studies (4-7, 13); (2) a high correlation has been reported for these mice between Penh values and lung resistance (14)(15)(16), and (3) we have established laboratory protocols in BALB/c mice for investigating the effects of in utero SHS exposure on adult lung responses to environmental irritants (3,11). Control groups without OVA challenge were not included in the study because our previous studies revealed that adult mice exposed in utero to SHS, but not exposed as adults to environmental stressors, do not exhibit signs of inflammation compared with the AIR mice (3,11).…”
Section: Discussionmentioning
confidence: 99%